Effect of hydraulic properties on slope stability in dual‐porosity soil - Tan, Tze Jung. (2013)
Slope stability has always been a major concern in geotechnical engineering. Studies have shown that it is possible to improve the slope analyses by taking negative pore-water pressure into consideration. Numerous analyses on slope stability have been conducted for slope with unimodal soil. However, there are very limited numbers of slope analyses conducted for soil with dual porosity.